2012
DOI: 10.1007/s13197-012-0674-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, molecular weight distribution, secondary structure and effect of NaCl on functional properties of walnut (Juglans regia L) protein isolates and concentrates

Abstract: Chemical composition, molecular weight distribution, secondary structure and effect of sodium chloride concentration on functional properties of walnut protein isolates, concentrates and defatted walnut flour were study. Compared with walnut protein concentrates (75.6%) and defatted walnut flour (52.5%), walnut protein isolates contain a relatively high amount of protein (90.5%). The yield of walnut protein isolates and concentrates was 43.2% and 76.6%, respectively. In molecular weight distribution study, Wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
3
21
4
Order By: Relevance
“…The solution was centrifuged for 15 min at 8586 × g (4°C), and the supernatant were filtered through a 0.22 μm cellulose membrane filter and analyzed by a Waters GPC system (515 HPLC Pump), equipped with a Waters HSPgel™ AQ 3.0 column (6.0 × 150 mm) and a Waters 2489 UV detector (Mao and Hua 2014). Following chromatographic conditions were applied: injection volume = 20 μl; isocratic flow rate = 0.3 ml/min; elution solvent = Milli-Q water containing 0.3 M NaCl; and run time = 15 min.…”
Section: Molecular Weight (Mw) Determination By Gel Permeation Chromamentioning
confidence: 99%
“…The solution was centrifuged for 15 min at 8586 × g (4°C), and the supernatant were filtered through a 0.22 μm cellulose membrane filter and analyzed by a Waters GPC system (515 HPLC Pump), equipped with a Waters HSPgel™ AQ 3.0 column (6.0 × 150 mm) and a Waters 2489 UV detector (Mao and Hua 2014). Following chromatographic conditions were applied: injection volume = 20 μl; isocratic flow rate = 0.3 ml/min; elution solvent = Milli-Q water containing 0.3 M NaCl; and run time = 15 min.…”
Section: Molecular Weight (Mw) Determination By Gel Permeation Chromamentioning
confidence: 99%
“…Studies of walnut protein or peptides were reported previously, e.g., the chemical composition, molecular weight distribution of walnut protein isolates and concentrates [17], the effect of different oil extraction methods on protein characteristics of walnut [18], and the antioxidant activities of the walnut hydrolysates [19]. Statistics show that China's walnut production is ranked first globally, but it is still far from self-sufficient in terms of processing capabilities and utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Olive oil contains few omega 6 and omega 3 fatty acids with 9.0% and 1.0%, respectively, and macadamia oil contains 3.22 % of omega 6 and 1.79% of omega 3 ( Table 2). Kahai oil has a similar profile of fatty acids when it is compared to walnut Juglans regia with a high content of omega 6 and a good content of omega 9, both oils presenting a few content of omega 3 [10,11]. Walnut has been considered as a healthy food due to its capacity to reduce cardiovascular diseases risk.…”
Section: Carrillo Et Almentioning
confidence: 99%